The Impact of Micro Finance Institutions on Growth of Small and Medium Enterprises: A Case Study of Pride Micro Finance in Mukono - Nelson Mandela (Uganda Christian University, 2023)
Finance and its associated services are a crucial prerequisite in the initiation and progress of the SMEs. The Impact of Microfinance on the Growth of the Small and Medium Enterprises in Mukono District was the main objective. To address, the study purpose, the study specifically addresses the following study objectives that are; products offered by MFIs to SMEs, how to access the products and constraints faced in the process by the SMEs of Mukono District. The study examined these products as that are three which are credit, savings and financial education. These products other stimulate financial indicators of growth or non-financial indicators of growth. The study used only cross-sectional research design supported by quantitative approaches. Using simple random sampling method, 200 SME operators were selected as a sample size thus received feedback from 133 SMEs in Mukono District was retrieved, having a response rate of 66.5%. The correlation results using the spearman’s rank correlation test show that savings, loan services and financial education had a high significant impact on the Growth of SMEs in Mukono District. According to the uncovering, the study concluded that loans services, savings deposits, financial education, and the different policies on credit play a fulcrum role on growth of SMEs in Mukono District. The study recommended that there should be training of SMEs in accessing, borrowing and utilization of loans received from MFIs, ensure that the terms of accessing savings from MFIs by SMEs are simplified to quicken access to their savings, provide enough loan repayment period to the SME operators since this would provide space for them to pay loans.
This is a dissertation.